The Effect of Street Theater on the Kurdish Theater Movement - Zhilwan Tahir Bapir; Kaify Ahmed Abdulqadir (Zanco Journal of Humanity Sciences)
The research entitled (The effect of street theater on the Kurdish theater movement) deals with an analytical study, which shades light on street theater, and is considered one of the direction of the theater published in all world countries, on the basis of intellectual, artistic and aesthetic. The research consists of three chapters. The first chapter (the methodological framework) deals with several points such as: the problem of the study, the importance of the study, the aim of the study and limits of the study. As for the second chapter (theoretical framework), it dealt with the subjects such as: the beginning and emergence of street theater and open space, experiences of street theater in countries around the world, the role of director and actor in street theater, stages of street theater preparation. As for the third chapter, it dealt with three theater models in street theater, and the research in the fourth chapter reached a number of results, the most important of which are: 1. In street theater, the actor and the receiver participate directly in the formation of the theater performance. 2. Improvisation plays an influential role in the installation of street theater show.